Clima laboral y desempeño del personal del Centro de Salud tipo a Calceta IESS período 2021 - Almeida Cedeño, Alisson Nicole (2023)
The present investigation was carried out with the purpose of evaluating the incidence of the work environment in the performance of the personnel of the health center type A Calceta IESS for the period 2021. This investigation of an exploratory descriptive nature, assisted by the deductive, synthetic analytical methods and the bibliographic review. In the first instance, it starts with the investigation of the theoretical bases of the work environment from the perspective of several authors through a meticulous bibliographic review in order to continue with the investigation of the legal regulations in force in the country referring to the object of study. As a second phase, the diagnosis of the factors that affect the work environment was carried out through the application of surveys to the institution's collaborators, where it is highlighted that such organization has the means, equipment and tools necessary for an efficient labor climate. Finally, the proposal for an improvement plan was developed, with the purpose of mitigating the inconveniences that were evident within the operational and administrative areas of the health center, and in this way the collaborators can have a better work environment, which is reflected in the labor efficiency and attention of the users. Therefore, it can be concluded that it is essential that the organization accept the proposed improvement plan and be socialized with all its collaborators with each of the strategies and activities imposed in it to reduce labor deficiency.